The Challenge of Ubiquitous Computing in Health Care: Technology, Concepts and Solutions - Bott, O. J.; Ammenwerth, E.; Brigl, B.; Knaup, P.; Lang, E.; Pilgram, R.; Pfeifer, B.; Ruderich, F.; Wolff, A. C.; Haux, R.; Kulikowski, C. (Methods of Information in Medicine, 2005)
Objectives: To review recent research efforts in the field of ubiquitous computing in health care. To identify current research trends and further challenges for medical informatics.Methods: Analysis of the contents of the Yearbook on Medical Informatics 2005 of the International Medical Informatics Association (IMIA).Results: The Yearbook of Medical Informatics 2005 includes 34 original papers selected from 22 peer-reviewed scientific journals related to several distinct research areas: health and clinical management, patient records, health information systems, medical signal processing and biomedical imaging, decision support, knowledge representation and management, education and consumer informatics as well as bioinformatics. A special section on ubiquitous health care systems is devoted to recent developments in the application of ubiquitous computing in health care. Besides additional synoptical reviews of each of the sections the Yearbook includes invited reviews concerning E-Health strategies, primary care informatics and wearable healthcare.Conclusions: Several publications demonstrate the potential of ubiquitous computing to enhance effectiveness of health services delivery and organization.But ubiquitous computing is also a societal challenge, caused by the surrounding but unobtrusive character of this technology. Contributions from nearly all of the established sub-disciplines of medical informatics are demanded to turn the visions of this promising new research field into reality.
Keywords: Medical informatics; health informatics; International Medical Informatics Association; ubiquitous computing; pervasive computing; mobile computing; yearbook